Anterior cruciate ligament reconstruction using bone plug-free quadriceps tendon autograft: intermediate-term clinical outcome after 24–36 months - Schulz AP; Lange V; Gille J; Voigt C; Fröhlich S; Stuhr M; Jürgens C (Dove Medical Press, 2013)
Arndt P Schulz,1 Vivien Lange,2 Justus Gille,1 Christine Voigt,3 Susanne Fröhlich,4 Markus Stuhr,1 Christian Jürgens5 1Department of Orthopedics, Trauma, and Sports Medicine, University Hospital Lübeck, Lübeck, Germany; 2Department of Rehabilitation, Sana Regio Klinikum, Wedel, Germany; 3Department of Sports Medicine and Arthroscopy, Diakoniekrankenhaus Friederikenstift, Hannover, Germany; 4Department of Orthopedics, University of Rostock, Rostock, Germany; 5Department of Orthopedics, Trauma, and Sports Medicine, BG Trauma Hospital Hamburg, Hamburg, Germany Introduction: Although known as a possible graft option for decades, quadriceps tendon grafts have often been termed a second-line graft option. We report a consecutive case series using this method as the primary treatment line. The rationale for this study was to evaluate the midterm results of this method in a prospective and consecutive case series. The primary study question was to determine the clinical results 24–36 months after primary anterior cruciate ligament (ACL) reconstruction using a bone plug-free quadriceps tendon autograft fixed with bioabsorbable cross-pins. Materials and methods: The study population included 55 patients, of whom 24 were female (43.6%). The mean age at the index procedure was 31.7 years (15–58 years). All patients received an ACL construction using a bone block-free quadriceps tendon graft fixed with resorbable cross-pins. The postoperative regimen included partial weight-bearing for 3 weeks and flexion limited to 90° for six weeks; an orthosis was not used. The mean follow-up duration was 29.5 months (24.3–38.5 months) after the index procedure. The International Knee Documentation Committee (IKDC) subjective score and examination form was assessed, as well as the Lysholm and Gillquist score and the Tegner activity index. The Rolimeter arthrometer was used to assess the anterior laxity of the knee. Results: Graft harvesting was possible in all cases; a bony extension was never required. On average, graft length was measured at 8.8 cm (7.5–10 cm). The mean IKDC subjective score at follow-up was 80.44 points (55.17–100 points, standard deviation [SD] 12.05). The mean preinjury Tegner activity index was 4.98 (2–7) compared to a mean value of 4.16 (2–7, SD 0.8) at follow-up. There was a mean loss of 0.82 index points. The average Lysholm and Gillquist score was 89 points (65–100, SD 17.7). Of the results, 89.1% were in the good or very good groups; in one case (1.8%), the result was poor, while the rest were fair. Conclusion: ACL reconstruction using a bone plug-free quadriceps tendon autograft achieved satisfactory results in a midterm review. Keywords: ACL reconstruction, arthroscopic treatment, quadriceps tendon, clinical case series